2017
DOI: 10.18178/ijiet.2017.7.4.883
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of e-Learning Environment: Can Social Presence Be Enhanced by Multimedia?

Abstract: Abstract-With the exponential development of Internet, distance learning has become an alternative means of taking a course or earning a degree. Social presence is a critical factor for forming and sustaining learning communities that support deeper learning through knowledge sharing. Social presence does not happen spontaneously and is in need of cultivation. This paper explores a review of the literature on social presence and the use of multimedia in distance education. The review of literature indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Further, majority of the survey students felt that instructors were providing good online lectures compared to physical education in universities. Moreover, student enrolment and satisfaction is linked to student success, teacher involvement and student retention in an online learning program [39].…”
Section: B Data Analysis and Findingsmentioning
confidence: 99%
“…Further, majority of the survey students felt that instructors were providing good online lectures compared to physical education in universities. Moreover, student enrolment and satisfaction is linked to student success, teacher involvement and student retention in an online learning program [39].…”
Section: B Data Analysis and Findingsmentioning
confidence: 99%
“…Furthermore, the instructor can show his/her care about students' learning, treat students with respect and impartiality, be approachable and available, and have realistic expectations. Alternatively, with the advance in information communication technology (ICT), the instructors may utilize various software applications such as AdobeConnect, Blackboard Collaborate, Citrix WebEx, and Zoom Video Communications to engage students and create a learning environment resembling a traditional face-to-face class (Lu, 2017;Thomas et al, 2014). ICT offers students the opportunity to have virtual real-time conversations with their peers and instructor.…”
Section: Instructor's Interventionsmentioning
confidence: 99%
“…In the higher education, the proliferation of online courses and programs continues to be a significant trend as an alternative to the traditional, face-to-face learning. This learning modality offers the students, greater convenience, flexibility, costeffectiveness, work-life-school balance (Travers, 2016) and the opportunity to complete the degree anywhere and anytime (Bowers and Kumar, 2015;Lu, 2017). Additionally, increasing demand from non-traditional, working adults who have both professional, family, and social responsibilities has driven the growth in online learning (Cochran, Cambell, Baker, and Lees, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dilling et al (2020) conducted a research to determine if differences exist in teaching and social presence between traditional and online education environments and concluded that an equally strong teaching and social presence can be obtained in the online learning process. Even before the lockdown process, this issue was in question in the literature, and there are studies proving that physical barriers can be removed by integrating multimedia into the online classroom environment which in the very end increases social presence and students' learning experiences (Lu, 2017). So as the authors of the current study, the aim is to examine the relationship between social presence and academic self-efficacy of university sports management students in elearning process during confinement by Covid-19.…”
Section: Introductionmentioning
confidence: 99%